Legal Review of Sexual Violence Against Children (Analysis of Decision Number 243 K/Pid.Sus/2020) - Ramadhana, Widodo; Ayu Sartika Telaumbanua, Yohana; Wilfred Joshua Rohtuahdo Purba, Barryl; Safron, Ananda (PT. Multidisciplinary Press Indonesia, 2024)
The Indonesian nation is a nation that highly respects Human Rights because children are the generation that will continue the principles of Indonesian nation, all citizens, even those created by God as state assets that cannot be separated from their elements and must be protected by their rights. But in reality, chidren are victims of a lot of sexual violence. Thus, the Indonesian government is very concerned about it in its efforts to address this social problem. Children who experience sexual abuse need extra care because they are still developing members of society both physically and psychologically. Children in Law No. 35 of 2014 is a promising law that is expected to overcome the problem of sexual violence against children. In the home environment in particular, parents are expected to take care of their children. But in reality, parents are the ones who commit sexual violence.